Análisis de la variación del precio del concreto en Bogotá (2018)
At the moment of conceiving the construction of a housing project in Bogotá and in a large part of Colombia, one must take into account its own variables such as: the execution time and the purchase of the main inputs, which do not have a regulation. in its final price, which allows the market itself to regulate its changes. It is for this reason, that is inquired about the prices presented in the last ten years (2007-2017), where it is evidenced, through a statistical analysis of the concrete of different resistances (3000psi, 3500psi, 4000, psi and 5000psi ) the variations that have been presented, the correlation that this variation has in different periods of time, as well as the way in which the price can be affected by the CPI (consumer price index) that the market handles at the moment , where it is evident that there is no standard pattern in this topic, for which, the respective analysis of another vital variable in the subject is made: the supply and demand of the market.